KEBIJAKAN PENGAWASAN TERHADAP PERBANKAN SYARIAH DALAM SISTEM HUKUM DI INDONESIA - Andrew Shandy Utama (Jurnal Cahaya Keadilan, 2020)
At the time of the economic crisis in 1998, many conventional banks collapsed while Islamic banks were not affected. After the crisis, Islamic banking experienced significant development in Indonesia. The problem is what is the direction of policy regarding supervision of Islamic banking in the national banking system in Indonesia? The method used in this research is normative legal research using the statutory approach. Data sources used in this study are secondary data, namely data obtained from statutory regulations, scientific journals, and legal literature. The data collection technique used in this research is literature study. The data analysis technique used in this study is qualitative analysis. The results of this study are policies regarding supervision of Islamic banking in the national banking system in Indonesia towards a better direction. In Act Number 7 of 1992 and Act Number 10 of 1998 it is stated that supervision of Islamic banking is carried out by Bank Indonesia as the central bank. However, based on Act Number 21 of 2008, supervision of sharia banking is not only carried out by Bank Indonesia, but is also monitored internally by the Sharia Supervisory Board. After the ratification of Act Number 21 of 2011, supervision of Islamic banking moved from Bank Indonesia to an independent institution called the Financial Services Authority.